Quality Tuberculosis Care in Indonesia: Using Patient Pathway Analysis to Optimize Public–Private Collaboration - Surya, Asik (J Infect Dis, 2017)
BACKGROUND: Tuberculosis (TB) is the fourth leading cause of death in Indonesia. In 2015, the World Health Organization estimated that nearly two-thirds of the TB patients in Indonesia had not been notified, and the status of their care remained unknown. As such, Indonesia is home to nearly 20% of the world’s “missing” TB patients. Understanding where patients go for care may enable strategic planning of services to better reach them. METHODS: A patient pathway analysis (PPA) was conducted to assess the alignment between patient care seeking and the availability of TB diagnostic and treatment services at the national and subnational level in Indonesia. RESULTS: The PPA results revealed that only 20% of patients encountered diagnostic capacity at the location where they first sought care. Most initial care seeking occurred in the private sector and case notification lagged behind diagnostic confirmation in the public sector. CONCLUSIONS: The PPA results emphasize the role that the private sector plays in TB patient care seeking and suggested a need for differentiated approaches, by province, to respond to variances in care-seeking patterns and the capacities of public and private providers.